Hubungan antara Penggunaan Media Video Animasi dengan Pemahaman Cerita Fiksi Siswa Kelas III UPT SPF SD Negeri Cendrawasih Kota Makassar - Aliem Bahri; Putri, Anastasya; Tarman A Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this research is to determine the relationship between the use of animated video media and the understanding of fictional stories among third-grade students. This study employed a descriptive correlational research design aimed at determining the relationship between the use of animated video media and students’ understanding of fictional stories in the third grade at UPT SPF SD Negeri Cendrawasih Makassar City. The population of this study consisted of all third-grade students at UPT SPF SD Negeri Cendrawasih Makassar City. The sample investigated was class III.A, consisting of 23 students, selected using purposive sampling technique. The variables measured were the use of animated video media and students’ understanding of fictional stories. The use of animated video media was measured using an observation sheet conducted during the learning process, while students’ understanding of fictional stories was obtained from the results of a comprehension test. The results of descriptive statistical analysis showed that the use of animated video media among third-grade students was quantitatively categorized as very good with an average score of 37.3, and the results of the fictional story comprehension test were quantitatively categorized as good with an average score of 81.1. Simple correlation analysis was used to test the relationship between the use of animated video media and students’ understanding of fictional stories. The results of the study involving 23 respondents showed that the calculated correlation coefficient (r-count) was 0.770, while the r-table value was 0.413. This indicates that the calculated correlation value was higher than the r-table value. Based on the findings above, it can be concluded that the use of animated video media has a relationship with the understanding of fictional stories among third-grade students at UPT SPF SD Negeri Cendrawasih Makassar City.